Automation Control Strategies for Intelligent Warehousing Systems - Shengtao Lin (Innovation in Science and Technology, 2025)
This paper focuses on intelligent warehousing systems, aiming to significantly enhance the automation and intelligence level of warehouse operations through innovative automation control strategies. It thoroughly analyzes the requirements of intelligent warehousing systems and the limitations of existing technologies, and designs a comprehensive control strategy covering path planning, task allocation, and fault handling. A software prototype is further developed and rigorously tested in a simulated environment to verify the effectiveness of the strategies. The research results indicate that the proposed control strategies can greatly optimize operational efficiency, reduce labor costs, and improve system reliability, providing strong support for the practical application of intelligent warehousing systems and promoting the development of the warehousing industry towards efficiency and intelligence.